2022
DOI: 10.1038/s41467-022-32172-9
|View full text |Cite
|
Sign up to set email alerts
|

Inverse altitude effect disputes the theoretical foundation of stable isotope paleoaltimetry

Abstract: Stable isotope paleoaltimetry that reconstructs paleoelevation requires stable isotope (δD or δ18O) values to follow the altitude effect. Some studies found that the δD or δ18O values of surface isotopic carriers in some regions increase with increasing altitude, which is defined as an “inverse altitude effect” (IAE). The IAE directly contradicts the basic theory of stable isotope paleoaltimetry. However, the causes of the IAE remain unclear. Here, we explore the mechanisms of the IAE from an atmospheric circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Previous studies have revealed that precipitation associated with the continental moisture from the west and northwest was characterized by more enriched isotopic compositions and higher d -excess values than the oceanic moisture sources , and reported the higher contribution of the continental source responsible for the higher precipitation δ 18 O and d -excess values at the seasonal time scale. , Therefore, spatially, it is reasonable to infer that precipitation upstream along the upper Jinsha River may be characterized by more enriched isotopic compositions and higher d -excess values as a result of the contribution from the westerly. A recent study has explored the mechanisms of the inverse isotopic altitude effect from an atmospheric circulation perspective using water vapor isotopes on the global scale . It was believed that the moisture supply with higher isotopic values from distant source regions and the strong lateral mixing along the moisture transport pathway were responsible for the inverse isotopic altitude effect, which emphasized that this phenomenon has already appeared in water vapor before precipitation and was further inherited by precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that precipitation associated with the continental moisture from the west and northwest was characterized by more enriched isotopic compositions and higher d -excess values than the oceanic moisture sources , and reported the higher contribution of the continental source responsible for the higher precipitation δ 18 O and d -excess values at the seasonal time scale. , Therefore, spatially, it is reasonable to infer that precipitation upstream along the upper Jinsha River may be characterized by more enriched isotopic compositions and higher d -excess values as a result of the contribution from the westerly. A recent study has explored the mechanisms of the inverse isotopic altitude effect from an atmospheric circulation perspective using water vapor isotopes on the global scale . It was believed that the moisture supply with higher isotopic values from distant source regions and the strong lateral mixing along the moisture transport pathway were responsible for the inverse isotopic altitude effect, which emphasized that this phenomenon has already appeared in water vapor before precipitation and was further inherited by precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has explored the mechanisms of the inverse isotopic altitude effect from an atmospheric circulation perspective using water vapor isotopes on the global scale. 50 It was believed that the moisture supply with higher isotopic values from distant source regions and the strong lateral mixing along the moisture transport pathway were responsible for the inverse isotopic altitude effect, which emphasized that this phenomenon has already appeared in water vapor before precipitation and was further inherited by precipitation. The surface water sample at a particular sampling site represents the integration of upstream precipitation and baseflow in the basin.…”
Section: 3mentioning
confidence: 99%
“…Everest and a number of meridional canyons), central Himalayas have sparse meteorological observation stations. In comparison, stable hydrogen and oxygen isotopes can fingerprint water sources as they are sensitive to environmental changes and can record water cycle information and trace moisture transport (Bowen & Wilkinson, 2002;Jing et al, 2022;Konecky et al, 2019;Yao et al, 2013;Yu et al, 2021;J. Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is likely to be valid because Huascarán is a tall and isolate mountain peak, which could be treated virtually as a passive "weather tower" that does not disturb the environment atmospheric circulation and in turn the isotope lapse significantly. In some other regions of high plateaus, such as the Tibetan Plateau and the Altiplano, the largescale topography can strongly disturb the atmospheric convection and the local isotope lapse rate, even leading to reversed isotopic lapse rate (83)(84)(85).…”
mentioning
confidence: 99%